Les rhétoriciens bruxellois issus de l’immigration et leur premier vote - Céline Teney; Dirk Jacobs (Brussels Studies)
In recent years, Belgians with an immigrant background have become an important electoral force in Belgian cities and in particular in the Brussels-Capital Region. Literature on the choice of parties and the voting characteristics of Belgians with an immigrant background is, however, lacking. In this article, we shall present the first analysis of the electoral charac-teristics of young students with an immigrant background in the Brussels-Capital Region who were voting for the first time in 2007. We have attempted to determine whether pupils with a non-European immigrant background have a special electoral profile which cannot be explained by other sociodemographic characteristics, such as their socioeconomic status or their educational orientation. Contrary to our expectations, after controlling a series of medi-ating variables, the country of birth of the mother of young students, still has a significant impact on their voting intentions.